Analysis and Design of User Interface Design and Using SWOT Concept for Optimizing Canteen Services - Rizki Candra Dermawan; Fajar Masya (Jurnal Sistem Informasi dan E-Bisnis, 2021)
For canteen and food court services optimization, a sistem is needed which able to handle problems, such as full table and consumers have to wait, a long queue of payments and must submit proof of payment to the seller so that food is prepared. Android-based E-CANTEEN application has features such as desk booking, so consumers don't have to worry about don’t get a table, food ordering, so consumers can order food before coming to the canteen and don't have to wait long for food ordered, internal e-wallet in a balance form so there is no need to queue to pay, unless Top-up the e-wallet balance. Consumers don’t have to go back to the seller's booth to show proof of payment, e-wallet reduces the risk of a small cash problem, all records on the E-CANTEEN sistem will be stored in the database thereby reducing printing costs, and avoiding the risk of spillage. The information sistem design using SDLC methods meanwhile business process analys using SWOT methods. Keywords:E-CANTEEN, e-wallet, SDLC, SWOT.